Compensation for Service Time - Álvarez Ramírez de Piérola, Fernando (1985)
This paper deals with the regulations on the Compensation -or “Indemnity”- for Time of Services (CTS), a fundamental legal institution in Peruvian labor legislation. This benefit applies in all cases of termination of the employment contract, regardless of the cause. By its nature, it constitutes a remuneration independent of the remuneration to which the employee is entitled on an annual basis for the energy expenditure experienced during such period. Along these lines, the legal provisions that must be followed to determine the amount of the CTS are explained, taking into account the employee's remuneration at the time of termination and his accumulated service time. Next, the different situations that affect the compensation are explained, and in turn, the special regimes applicable to specific sectors that have particular rules for the calculation and payment of the CTS are mentioned. Finally, the author argues that the CTS, like other social benefits, is supported by Peruvian law and is considered a fundamental right to guarantee the economic stability of workers once their employment relationship ends.